2017
DOI: 10.1186/s13287-017-0563-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as potential alternatives to stem cell therapy for intervertebral disc degeneration: in-vitro study on exosomes in interaction of nucleus pulposus cells and bone marrow mesenchymal stem cells

Abstract: BackgroundThe stem cell-based therapies for intervertebral disc degeneration have been widely studied. However, the mechanisms of mesenchymal stem cells interacting with intervertebral disc cells, such as nucleus pulposus cells (NPCs), remain unknown. Exosomes as a vital paracrine mechanism in cell–cell communication have been highly focused on. The purpose of this study was to detect the role of exosomes derived from bone marrow mesenchymal stem cells (BM-MSCs) and NPCs in their interaction with corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(143 citation statements)
references
References 35 publications
5
136
0
2
Order By: Relevance
“…Studies have revealed that MSC medium may contain a large amount of protective factors for NICCs exposed to hypoxic damage, 51 and exosomes are one example. 52,53 Exosomes are membrane- clinically relevance, we have tested clinical serum-free medium (Cell Therapy Systems STEMPRO MSC SFM CTS medium (Thermofisher, A10332-01) in our culture system and achieved similar results to that presented in this study. Exosomes derived from MSCs might be an efficient nutrient delivery vehicle for graft islets, and may become a promising strategy to improve the outcome of islet transplantation.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Studies have revealed that MSC medium may contain a large amount of protective factors for NICCs exposed to hypoxic damage, 51 and exosomes are one example. 52,53 Exosomes are membrane- clinically relevance, we have tested clinical serum-free medium (Cell Therapy Systems STEMPRO MSC SFM CTS medium (Thermofisher, A10332-01) in our culture system and achieved similar results to that presented in this study. Exosomes derived from MSCs might be an efficient nutrient delivery vehicle for graft islets, and may become a promising strategy to improve the outcome of islet transplantation.…”
Section: Discussionsupporting
confidence: 63%
“…Studies have revealed that MSC medium may contain a large amount of protective factors for NICCs exposed to hypoxic damage, and exosomes are one example . Exosomes are membrane‐enclosed nanovesicles (50‐200 nm diameter in our test) that shuttle active cargo between different cells.…”
Section: Discussionmentioning
confidence: 81%
“…And it was demonstrated that MSCs influenced NP cells via paracrine manner, cell contact, and cell fusion, promoting NP cells to secrete cytokines that induced the differentiation of stem cells to NP-like cells, and these cytokines could also facilitate NP-like cells to repair IVD degeneration 84,85 . It was also reported that NP cells could secrete exosomes to induce bone marrow-derived MSCs differentiation to NP-like cells and promote bone marrow-derived MSCs migration 86 .…”
Section: Interactions Between Exogenous Mscs and Np Cellsmentioning
confidence: 99%
“…It was reported that NPC‐derived exosomes promoted MSC migration and stimulated MSCs to differentiate to a nucleus pulposus–like phenotype. MSC‐derived exosomes also stimulated the NPCs to regain a nondegenerate phenotype and enhance extracellular matrix production . This study suggests that the exosome‐based, cell‐free/progenitor therapeutic approach bears potential for IVD treatment.…”
Section: Stem Cell–derived Exosomes: Emerging Role In Musculoskeletalmentioning
confidence: 70%
“…MSCderived exosomes also stimulated the NPCs to regain a nondegenerate phenotype and enhance extracellular matrix production. 88 This study suggests that the exosome-based, cell-free/progenitor therapeutic approach bears potential for IVD treatment.…”
Section: Stem Cell-derived Exosomes: Emerging Role In Musculoskeletalmentioning
confidence: 80%